Mitigating the shadow of conflict: the role of social and human capital for the reduction of conflicts - Dorothee Schmidt (Max Planck Institute for Research on Collective Goods, 2007)
One possible solution to mitigate the negative influences of conflict which has been proposed in the literature is to subject the relevant parties to education. Education can take two forms: increasing an individual's human capital on the one hand, increasing her social capital on the other hand. Using a stylized model of a two-individual economy, we derive that increasing an individual's social capital will lead her to reduce her conflict effort, whereas increasing her human capital can induce her to increase her conflict effort. We then analyze which conditions need to be present to induce the individuals to invest into their social capital.
Keywords: D72; D74; I28; K42; Z13; 300; Contests; conflict reduction; education; human capital; social capital; morality; Konflikt; Bildungsinvestition; Social Capital; Wettbewerb; Wirtschaftsethik; Theorie